PMTCT Option B+ 2012 to 2018 — Taking stock: barriers and strategies to improve adherence to Option B+ in urban and rural Uganda. Issue 2 (2nd April 2020) - King, Rachel; Matovu, Joyce Namale; Rujumba, Joseph; Wavamunno, Priscilla; Amone, Alexander; Gabagaya, Grace; Fowler, Mary Glenn; Homsy, Jaco; Seeley, Janet; Musoke, Philippa
Abstract : Since 2012, PMTCT Option B+ has been recommended by the World Health Organization to reduce vertical transmission but numerous adherence challenges remain. We conducted a qualitative study at baseline using six focus group discussions and 14 in-depth interviews to explore knowledge, beliefs, attitudes and challenges towards the Option B+ strategy for PMTCT among HIV-infected pregnant and post-partum women and health workers engaged in Uganda's national Option B+ PMTCT programme. Data were analysed using a thematic approach to capture latent and manifest content with the social ecological model as a theoretic foundation in order to make contextual sense of key stakeholders' needs for an effective Option B+ intervention. Overall, among all study participants, we found multi-level barriers to adhering to Option B+ cutting across all levels of the social ecological model. In line with the model, our study revealed barriers at personal, relational, organizational and societal levels. Some personal beliefs such as that the baby's health is more important that the mother's, organizational (negative attitudes and behaviour of health workers), structural such as poverty, work conflicts, fear and lack of disclosure related to community stigma were all critical obstacles to women adhering to the Option B+ programme. We found that both health workers and participants in the programme have a relatively clear understanding of the benefits of adhering to their treatment; though a more nuanced understanding and thus emphasis in counselling on side effects, is critical to helping patients adhere.